Assessment of exocrine pancreatic function by secretin‐stimulated magnetic resonance cholangiopancreaticography and diffusion‐weighted imaging in healthy controls. Issue 2 (6th May 2013) - Wathle, Gaute K.; Tjora, Erling; Ersland, Lars; Dimcevski, Georg; Salvesen, Øyvind O.; Molven, Anders; Njølstad, Pål R.; Haldorsen, Ingfrid S.
<x xml:space="preserve">Abstract</x> Purpose To characterize and quantify exocrine pancreatic function by secretin‐stimulated magnetic resonance cholangiopancreaticography (s‐MRCP) and diffusion‐weighted imaging (DWI) in healthy subjects and compare these findings to morphological features, ie, pancreatic volume and secretin‐stimulated peak bicarbonate concentration measured in pancreatic juice. Materials and Methods Pancreatic magnetic resonance imaging (MRI) (1.5 T) was performed in 20 healthy volunteers among which 10 underwent gastroscopy with duodenal intubation. MRI included T2‐weighted imaging and DWI acquired before and 1, 5, 9, and 13 minutes after secretin administration. Secreted pancreatic juice volumes were calculated based on the sequential T2‐weighted images and pancreatic volumes and apparent diffusion coefficient (ADC) values were estimated. Results The mean pancreatic secretion rate declined from 9.5 mL/min at 1–5 minutes (postsecretin) to 2.9 mL/min at 9–13 minutes. Pancreatic head ADC values significantly increased from baseline (1.29 × 10−3 mm2/s) to 1 minute postsecretin (1.48 × 10−3 mm2/s) (P = 0.003). Secreted pancreatic juice volume at 1 minute after secretin correlated positively with peak bicarbonate concentration (n = 10, P = 0.05). Conclusion Secretin‐stimulated MRCP and DWI can characterize and quantify exocrine pancreatic function in healthy subjects. These imaging methods may prove relevant for patients with exocrine pancreatic dysfunction. J. Magn. Reson. Imaging 2014;39:448–454. © 2013 Wiley Periodicals, Inc.